2019
DOI: 10.1002/btpr.2898
|View full text |Cite
|
Sign up to set email alerts
|

Fast flow rate processes for purification of alkaline xylanase isoforms from Bacillus pumilus AJK and their biochemical characterization for industrial application purposes

Abstract: This study shows the presence of five isozymic forms of alkaline xylanase from Bacillus pumilus using fast flow rate microfiltration, ultrafiltration, Q-sepharose, and phenyl sepharose chromatographic techniques. Polyacrylamide gel electrophoresis, highperformance liquid chromatography, and zymographic studies also revealed the purity of five isoforms of alkaline xylanases. Isoforms-X-I, X-III, and X-V exhibited optimum activity at pH 8.5, whereas X-II, X-IV showed maximum activity at pH 9. All isoforms were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The fractions were combined according to the number of elution peaks to gather them. After dialyzing, freeze-drying, and concentrating, the fractions which include AR-9 were obtained ( Li et al, 2018 ; Singh et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The fractions were combined according to the number of elution peaks to gather them. After dialyzing, freeze-drying, and concentrating, the fractions which include AR-9 were obtained ( Li et al, 2018 ; Singh et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This shows that species identification may not be a good predictor of their ability to express any given enzyme; these traits may only be traceable for a given strain and not evenly distributed for all strains within a given species. Shakir et al [45] reported a B. licheniformis-producing xylanase, and Singh et al [46] described xylanase production from B. pumilus. Among the isolates obtained in this study, the other Bacilli expressing extracellular xylanase activity in agar media were B. subtilis 2Aq, B. velezensis 6Aq, B. licheniformis 15Aq, B. subtilis 23Aq, and B. tequilensis 18Aq and 26Aq.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at https://www. mdpi.com/article/10.3390/foods12193574/s1, see refs [42][43][44][45], Table S1: The preparation of optimal temperature and thermostability of various enzymes.…”
Section: Supplementary Materialsmentioning
confidence: 99%